2006
DOI: 10.1093/deafed/enl011
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Skills in a Semistructured Interview and Self-Concept in Deaf Students

Abstract: The starting point for this study is the importance of linguistic competence in deaf students as part of their process of socialization and the formation of their self-concept. With the 56 deaf students who participated in the research, we consider the following sociodemographic variables: age, sex and degree of hearing loss, and the educational factor with respect to the mode of mainstream schooling. Self-concept was explored using the Spanish version of the Self Development Questionnaire (SDQ; I. Elexpuru, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
2
13
0
2
Order By: Relevance
“…mainstream versus segregated provision) in deaf or hard-ofhearing children, but that self-image may vary with the setting when the child's language skills are also taken into account. This is supported by the findings of Silvestre et al (2007), who reported a significant association between positive self-concept and conversational competence. Where self-esteem is found to be lower in mainstreamed, oral school placements, this may be the result of mainstreamed children feeling 'different' and experiencing teasing or bullying by majority hearing groups, whereas those attending Deaf schools are part of a majority culture with a positive, affirming view of Deafness.…”
Section: Introductionsupporting
confidence: 75%
“…mainstream versus segregated provision) in deaf or hard-ofhearing children, but that self-image may vary with the setting when the child's language skills are also taken into account. This is supported by the findings of Silvestre et al (2007), who reported a significant association between positive self-concept and conversational competence. Where self-esteem is found to be lower in mainstreamed, oral school placements, this may be the result of mainstreamed children feeling 'different' and experiencing teasing or bullying by majority hearing groups, whereas those attending Deaf schools are part of a majority culture with a positive, affirming view of Deafness.…”
Section: Introductionsupporting
confidence: 75%
“…The relation between the hearing researcher and young deaf people is characterised by another form of asymmetry (Silvestre, Ramspott, and Pareto 2007;Punch and Hyde 2011). The question 'deaf or hearing' comes up recurrently during the first face-to-face interactions with the interviewees.…”
Section: European Journal Of Special Needs Educationmentioning
confidence: 99%
“…In [5] as well as [6] stipulated that individuals with hearing impairment faces problems in communication and are not able to make themselves understood by normal person. This situation affects the social, emotional and cognitive development of the hearing-impaired [7] and play a pivotal role in their overall psychological wellbeing.…”
Section: Introductionmentioning
confidence: 99%